The Politics of Postliteracy. - Callahan, Gene (Modern Age)
This article centers on Mary Harrington’s analysis of the cultural and political transformations initiated by the printing press and their ongoing disruption by digital technologies, particularly smartphones. Harrington argues that the printing press was foundational to modernity, enabling scale and fixity in knowledge that shaped nation-states, democracy, and secularism, while literacy fundamentally altered human cognition. She contends that the digital revolution, marked by the smartphone’s ubiquity, represents a new "singularity" that is reshaping social interaction, political organization, and cognitive habits, leading to a postliterary age with uncertain political forms, possibly more autocratic or tribalized. Harrington also discusses the feminization of work as influenced by sociocultural and technological environments rather than solely by gender, and she expresses skepticism about dystopian visions of totalitarian capitalism, suggesting demographic and cognitive declines may instead drive future societal change.